Evaluation Of Risk Factors In Perforated Acute Appendicitis In Al-Kindy Teaching Hospital - Hindosh, Laith Naif; Kamal, *Zuhair Basheer; Rezqallah, Raed Esttaifan (AL-Kindy College Medical Journal, 2016)
Background: Appendectomy is still one of the most commonly performed emergency surgical procedures worldwide.Avoiding delays in the diagnosis in these patients may play a role in reducing observed morbidity.Aim of study:To analyze the clinico-pathological profile and outcomes of patients undergoing emergency appendectomies to determine risk factors influencingcomplicaions.Type of the study: A prospective analytic studyPatients and Methods: The study involves 108 patients underwent emergency appendectomies at Al-kindy teaching hospital from April 2014 to March 2015. Appendicitis was categorized into two groups perforated andnonperforatedappendicities. A comparison between them was made in regard to Gender, Age, clinical presentation, investigations(White blood cells count), patient’s delay, hospital delay, anatomical location of the appendix, presenceof fecolith.Results: Five factors were predicted that influence appendicealrupture,the patient’s pre-hospital time delay was the most important risk factor for perforation. The male are slightly more affected than female in a percentage of (60male) 55.55% and (48female) 44.44%.The most common appendix anatomical location for complicated appendicitis was pelvic 16 out of 32 (50%).The presence of fecolith in the lumen of appendix was considered significant risk factor for perforation 23/32 (71.875%). In the perforated group 28patients out of 32had high White blood cells count(87.5%) compared to patients in the non-perforated group36 (47.39%).Conclusions:Young age group, male gender, pelvic anatomical location of the appendix ,presence of faecolith in the lumen of the appendix and prehospital time delay were found to be the most important risk factors